Tri(supersilyl)dialanyl (tBu3Si)3Al2• and tetra(supersilyl)cyclotrialanyl (tBu3Si)4Al3•: new stable radicals of a group 13 element from thermolysis of (tBu3Si)4Al2 - Wiberg, Nils; Blank, Thomas; Kaim, Wolfgang; Schwederski, Brigitte; Linti, Gerald W. (European journal of inorganic chemistry, 2000)
The thermolysis of tetra(supersilyl)dialane R*2Al−AlR*2 (R* = SitBu3 = Supersilyl) in heptane or cyclohexane at 50 °C leads under Al−Al dissociation reversibly to monoalanyl radicals [R*2Al]•, which could...